Telerehabilitation proposal of mind-body technique for physical and psychological outcomes in patients with fibromyalgia - Paolucci, Teresa; de Sire, Alessandro; Ferrillo, Martina; di Fabio, Dania; Molluso, Aurora; Patruno, Antonia; Pesce, Mirko; Lai, Carlo; Ciacchella, Chiara; Saggino, Aristide; Agostini, Francesco; Tommasi, Marco (Frontiers in Physiology, 2022)
Fibromyalgia (FM) syndrome is characterized by the close correlation of chronic widespread pain and other non-pain related symptoms. Aim of this study was to investigate whether telerehabilitation that provides physical and psychological support services of the mind-body techniques can affect the clinical profile and pain relief of FM patients. The study included twenty-eight female FM patients, mean aged 56.61±8.56 years. All patients underwent a rehabilitation treatment (8 sessions, 1/week, one hour/each) through Zoom platform, with the following principles of rehabilitation treatment: anchoring to a positive emotion; listen and perceive your "own" body; conscious breathing; improve interoceptive awareness; relax. All patients then underwent clinical assessment of the physical distress and fear of movement for the Numeric Rating Scale (NRS); the Fatigue Assessment Scale (FAS); the Fear Avoidance Belief Questionnaire (FABQ); with measures of physical and mental disability for the Fibromyalgia Impact Questionnaire (FIQ); the 12-Items Short Form Survey; the Resilience Scale for Adults and the Coping Strategies Questionnaire-Revised. The evaluations were performed at T0 (baseline), T1 (after 8 weeks of treatment), and T2 (after one month of follow-up). The main finding was that telerehabilitation reduced physical and mental distress, fear, and disability (p<0.001). Resilience and coping ability were less affected by the rehabilitative treatment. Our attempt of mind-body technique telerehabilitation has shown good results in the improvement of painful symptoms and quality of life for the FM patients but showed fewer positive impacts for the resilience and coping abilities aspects.